Critical Reflexivity and Moral Regulation. Issue 1 (2nd January 2016) - Badwall, Harjeet
ABSTRACT: Critical reflexivity is a dominant practice framework in social work. It is designed to address the operation of power relations between social workers and their clients. However, I intend to shed light on a different set of concerns related to this practice. I examine the ways in which critical reflexivity can operate to re-inscribe colonial notions of moral superiority, and re-center whiteness within social work education and practice settings. Drawing on research I conducted with racialized social workers in Toronto, Canada, this article examines the ways in which critical reflexivity can operate as a governing technology to silence the operation of racism.